2002
DOI: 10.1007/s00432-001-0305-2
|View full text |Cite
|
Sign up to set email alerts
|

p53 Gene status in relation to ex vivo chemosensitivity of non-small cell lung cancer

Abstract: Mutations in the p53gene can lead to enhanced chemoresistance, confirming the hypothesis that the p53 gene may serve as a marker of tumor response to treatment in NSCLC. However, the data also illustrate that some additional factors might contribute to drug resistance of the examined tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…7 Accumulating evidence, however, suggests that mutant TP53 confers the chemo-resistance of cancer cells in vitro and vivo. 8,9 The research by Ludovini et al 10 showed that mutant TP53 is apparently related to the recurrence of NSCLC, indicating its function as a poor prognostic factor. Key words: non-small cell lung cancer, targeted therapy, p53, hypoxia, TAT, oxygen-dependent degradation domain, solid tumor…”
Section: Introductionmentioning
confidence: 99%
“…7 Accumulating evidence, however, suggests that mutant TP53 confers the chemo-resistance of cancer cells in vitro and vivo. 8,9 The research by Ludovini et al 10 showed that mutant TP53 is apparently related to the recurrence of NSCLC, indicating its function as a poor prognostic factor. Key words: non-small cell lung cancer, targeted therapy, p53, hypoxia, TAT, oxygen-dependent degradation domain, solid tumor…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of this gene often result in loss of p53 function and p53 inactivation (12,13), contributing to aggressive tumor behavior and therapeutic resistance (14). Several reports have shown that the expression of wild-type p53 is necessary for the cytotoxic response to chemotherapeutic agents (15)(16)(17), although there are some conflicting results (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, wild-type p53 expression predisposes cells to a more rapid rate of cell death after DNA damage. Previous studies have reported that non-small cell lung cancer cells having p53 mutations showed significantly poorer response to intensive chemotherapy that included etoposide and epirubicin (Vogt et al, 2002). In addition, treatment of MCF-7 with doxorubicin resulted in an increase of p53 expression, confirming a p53-mediated response to doxorubicin in cells containing a wildtype p53 gene product (Liem et al, 2003).…”
Section: Discussionmentioning
confidence: 62%